Modern technologies enable treatment planning and the fabrication of clear aligners for the correction of misaligned teeth: Sodobne tehnologije omogočajo načrtovanje in izdelavo opornic za zdravljenje položajnih nepravilnosti zob - Fekonja, Anita; Rošer, Nejc; Drstvenšek, Igor (Acta Medico-Biotechnica, 2022)
Purpose: This article reports the realignment of teeth with clear aligners (CA) made using a modern technique manufactured entirely in Slovenia.Case report: A 34-year-old man visited the Orthodontic Department of our healthcare centre because of misaligned teeth in the mandibular arch. The goal of treatment was to align the mandibular anterior teeth using a Slovenian-made CA. The procedure began with an impression for the working cast that was scanned and a 3D image of the patient's dental arches and occlusion were created in the computer. A software package was used to create a 3D virtual model,and the teeth were virtually placed in the positions that would be achieved during treatment with the CA. The CA were made of an elastic thermoplastic material (polyurethane). The patient was instructed to wear the appropriate aligner for 22 hours daily and change it every two weeks. Dental crowding was corrected in six months and at the end of treatment a lingual fixed retainer was bonded to prevent relapse. The patient was very satisfied with the result. After two years of retention, the results remain stable.Results: Comparable to a conventional fixed appliance, a CA is a removable device that offers better aesthetics, more comfort and better oral hygiene.
Keywords: clear aligners, tooth alignment, digitization, additive manufacturing